EVALUATION OF ACETYLCHOLINESTERASE ACTIVITY AND CYTOTOXICITY OF DIFFERENT PARTS OF NELUMBO NUCIFERA GAERTN ON HUMAN NEUROBLASTOMA CELL LINE (SH-SY5Y) - JARMKOM, KHEMJIRA; TECHAOEI, SURACHAI; WISIDSRI, NAKUNTWALAI; KHOBJAI, WARACHATE (International Journal of Applied Pharmaceutics, 2019)
Objective: Cognitive deterioration occurring in patients with probable Alzheimer’s disease is associated with a progressive loss of cholinergic neurons and a consequent decline in levels of acetylcholine in the brain. This study aimed to evaluate the acetylcholinesterase (AChE) inhibitory effects and cytotoxicity in SH-SY5Y cells of different parts of three lotus extracts. Methods: AChE activity was quantified by spectrophotometry and cytotoxicity by flow 3-(4,5-dimethythiazol-2-yl)-2,5-diphenyltetrazolium bromide assay in SH-SY5Y cells exposed to extracts. Results: All of the extracts had inhibitory effects to AChE at p<0.05, but Roseum Plenum stem extract could inhibit AChE more than 30% (p<0.05). The all of the extracts could be an increase SH-SY5Y cell proliferation, while Album Plenum flower extract could be cytotoxic on SH-SY5Y cells. Conclusion: The extracts of lotus could be supplemented compound for cognitive deterioration or Alzheimer’s patients.